The Lithic Technology of the "Abdasan" and "Aougni N’Ourigh" Rock Shelters (Oukaïmeden Valley, High Atlas, Morocco) - de la Peña, Paloma (Complutum, 2014)
The main technological strategies of the lithic material of Abadsan and Aougni N’Ourigh are presented. The knapping methods and the techniques are specifically described following a chaîne opératoire approach. Moreover, the main knapping objectives are pointed out. Finally, some functional insights are proposed following the macroscopic traces found.